2016
DOI: 10.1371/journal.pone.0167414
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features and Prognosis of Papillary Thyroid Microcarcinoma for Surgery and Relationships with the BRAFV600E Mutational Status and Expression of Angiogenic Factors

Abstract: ObjectiveTo investigate the clinicopathological characteristics of papillary thyroid microcarcinoma (PTMC) for surgery by comparing the difference between PTMC and larger papillary thyroid carcinoma (LPTC).MethodsWe analyzed the differences in the clinicopathological characteristics, prognosis, B-type RAF kinase (BRAF)V600E mutational status and expression of angiogenic factors, including pigment epithelium-derived factor (PEDF), Vascular Endothelial Growth Factor (VEGF), and hypoxia-inducible factor alpha sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
4
16
3
Order By: Relevance
“…A previous study that analyzed the gene expression profiles of 25 pairs of thyroid microcarcinomas and normal counterparts, as well as 11 pairs of carcinomas and normal counterparts, found that the gene expression profiles of microcarcinomas were not different from those of carcinomas . Furthermore, there were no significant differences in the mRNA expression levels of pigment epithelium‐derived factor, vascular endothelial growth factor, and hypoxia‐inducible factor‐1α between high‐risk microcarcinomas and carcinomas . Our findings are in agreement with these reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A previous study that analyzed the gene expression profiles of 25 pairs of thyroid microcarcinomas and normal counterparts, as well as 11 pairs of carcinomas and normal counterparts, found that the gene expression profiles of microcarcinomas were not different from those of carcinomas . Furthermore, there were no significant differences in the mRNA expression levels of pigment epithelium‐derived factor, vascular endothelial growth factor, and hypoxia‐inducible factor‐1α between high‐risk microcarcinomas and carcinomas . Our findings are in agreement with these reports.…”
Section: Discussionsupporting
confidence: 92%
“…between high-risk microcarcinomas and carcinomas. 23 Our findings are in agreement with these reports. Before propensity matching, PCA revealed that microcarcinomas were virtually indistinguishable from larger carcinomas.…”
supporting
confidence: 94%
“…The worldwide incidence of thyroid cancer, especially papillary thyroid carcinoma (PTC), has increased rapidly in recent years [ 1 , 2 ]. Regional lymph node metastasis is commonly observed in PTC and occurs in approximately 30-80% of PTC patients [ 3 , 4 ], even in Papillary thyroid microcarcinoma (PTMC, ≤10 mm)[ 5 , 6 ], which may present an associated increased risk of regional recurrence and distant metastasis [ 7 ]. Previous studies reported that nodal metastasis of PTC occurs in a stepwise fashion, with metastasis beginning in the central cervical compartment, continuing to the ipsilateral cervical compartment, and finally arriving at the contralateral lateral or mediastinal compartment; therefore, the lateral compartment is the second site of PTC metastases [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…BRAF gene mutation are most closely related to PTC. Studies have shown that the BRAF V600E mutation is closely related to multifocality, lymph node metastasis, extrathyroidal extension and advanced-stage of PTC, thus predictive of poor prognosis of tumours [15,16]. However, because the mutation only exists in 40-45% of PTC patients, it has some limitations as a diagnostic and prognostic marker [15].…”
Section: Introductionmentioning
confidence: 99%